How democracy alters our view of inequality and what this means for wellbeing. (20th October 2021) - Gugushvili, A; Reeves, A
Abstract:  : Income inequality is associated with poor health when economic disparities are especially salient. However, political institutions may alter this relationship because democracies (as opposed to autocracies) may be more inclined to frame inequalities in negative rather than positive ways. Living in a particular political system potentially alters the messages individuals receive about whether inequality is large or small, good or bad, and this, in turn, might affect whether beliefs about inequality influence health. Further, media coverage of economic inequality may negatively affect health if it contributes toward the general perception that the gap between rich and poor has gone up, even if there has been no change in income differentials. In this study, we explore the relationship between democracy, perceptions of inequality, and self-rated health across 28 post-communist countries using survey and macro-level data, multilevel regression models, and inverse probability weighting to estimate the average treatment effect on the treated. We find that self-rated health is higher in more democratic countries and lower among people who believe that inequality has risen in the last few years. Moreover, we observe that people in democracies are more likely to learn about rising inequality through watching television and that when they do it has a more harmful effect on their health than when people in autocracies learn about rising inequality through the same channel, suggesting that in countries where there is less trust in the television media learning about rising inequality is not as harmful for health. Our results indicate that while democracies are generally good for well-being, they may not be unambiguously positive for health. This does not mean, of course, that inequality is good for health nor that, on average, autocracies have better health than democracies; but rather that being more aware of inequality can negatively affect wellbeing Key messages: While democracies are generally good for well-being, they may not be unambiguously positive for health. Being more aware of inequality can negatively affect wellbeing.